Pentingnya Literasi Keuangan Untuk Mengatasi Perilaku Konsumtif Di Kalangan Orang Muda Katolik - Karubun, Yuliana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2024)
This research starts from concerns about consumptive behavior which is most evident among OMK. The aim of this research is to explain the importance of financial literacy to overcome consumtive behavior among the Catholic youth. It employs a literature method using an exposition approach. The research results emphasize several reasons for the importance of financial literacy for the Catholic youth, which consists of theoretical knowledge that helps them to understand personal financial arrangements properly and correctly, as theoretical knowledge for OMK as Christian believers to better understand the Church's view of money as a means to improve the welfare of life. and not just as a goal to gain personal pleasure and as a guide for the author himself as a prospective Catholic Religious Education Teacher and wife so that he can manage family finances well and proportionally.